Plant Pigments obtained from Ultrasound-assisted Extraction: Color properties and Antioxidant Activities during in vitro Digestion - Liangpanth, Titikan -; Sasanatayart, Rungarun - (Food and Applied Bioscience Journal, 2020)
Herbal plants are potential sources of natural pigments, providing distinctive colors and exert antioxidant effects that are far more superior than synthetic colorants. The highly efficient extraction of natural colorants supports their use as substitutes for synthetic dyes in industrial applications. In this study, four major types of plant pigment including anthocyanins from butterfly pea flower (Clitoria ternatea L.), betalains from dragon fruit peel (Hylocereus undatus), curcuminoids from turmeric rhizome (Curcuma longa) and chlorophylls from pandan leaf (Pandanus amaryllifolius) were extracted with water and 50% (v/v) aqueous ethanol, compared with 70% (v/v) acidic acetone. Results showed that water was the most effective solvent for extraction of betalains and anthocyanins whereas, 50% (v/v) aqueous ethanol was suggested for extraction of curcuminoids and chlorophylls since it gave the higher concentration of the required pigment and the most intense color with higher antioxidant properties. In order to enhance extraction efficiency, ultrasound−assisted extraction (UAE, 38.5 kHz) was conducted at 25 and 65°C for 1 h, compared to maceration under agitation at 25°C for 24 h. Among extraction conditions, UAE apparently increased extraction efficiency compared to maceration with agitation. UAE at 25°C gave the highest concentration of the required pigments, total phenol content and associated antioxidant activities based on FRAP and DPPH. However, temperature during UAE at 65oC could also stimulate or inactivate antioxidant capacities of samples. To assess their stability and bioaccessibility, the four pigment solutions obtained from UAE at 25°C were compared. Upon in vitro gastrointestinal digestion, all pigment compounds, total phenolics and their antioxidant activities increased on gastric digestion (126.87−260.44% recovery) but, decreased during intestinal digestion (47.44−80.70% recovery). Their respective antioxidant capacities were also recovered 106.66−141.33% during gastric digestion and recovered 54.30−89.77% during intestinal digestion. Results revealed the low stability of pigment compounds and their associated antioxidant activities after gastrointestinal digestion.